2015
DOI: 10.1212/wnl.0000000000001742
|View full text |Cite
|
Sign up to set email alerts
|

Early EEG contributes to multimodal outcome prediction of postanoxic coma

Abstract: Objectives:Early identification of potential recovery of postanoxic coma is a major challenge. We studied the additional predictive value of EEG.Methods:Two hundred seventy-seven consecutive comatose patients after cardiac arrest were included in a prospective cohort study on 2 intensive care units. Continuous EEG was measured during the first 3 days. EEGs were classified as unfavorable (isoelectric, low-voltage, burst-suppression with identical bursts), intermediate, or favorable (continuous patterns), at 12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
292
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 224 publications
(306 citation statements)
references
References 32 publications
11
292
2
1
Order By: Relevance
“…Our findings show high specificity of a first unreactive EEG background for predicting poor outcome at 36°C. Besides background amplitude (31,32), reactivity has been repeatedly described (10,12,(33)(34)(35); however, as opposed to this study, those description rely on patients treated with 33°C and the first EEG recorded during TTM is generally not included as a predictor in current recommendations (28,36). We acknowledge that lack of standardized stimulations (24) remains a relevant limitation.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings show high specificity of a first unreactive EEG background for predicting poor outcome at 36°C. Besides background amplitude (31,32), reactivity has been repeatedly described (10,12,(33)(34)(35); however, as opposed to this study, those description rely on patients treated with 33°C and the first EEG recorded during TTM is generally not included as a predictor in current recommendations (28,36). We acknowledge that lack of standardized stimulations (24) remains a relevant limitation.…”
Section: Discussionmentioning
confidence: 94%
“…[20][21][22] Prior work has examined prognostic tests such as neurologic examination, SSEP, biomarkers, EEG, brain CT, and MRI in isolation. [9][10][11][12][13][14][15][16][17][18] Recent work has tested predictive value of multiple modalities, but the ideal combination is not known. [28][29][30][31][32] Importantly, not all tests are necessary for all patients and some facilities may not offer all of these modalities.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19] The combination of multiple modalities is recommended because no single test short of physical examination meeting brain death criteria can predict neurologic outcome correctly. [20][21][22] We previously reported that combining the initial neurologic examination with continuous EEG (cEEG) was superior to any individual test for predicting outcome after CA.…”
Section: Introductionmentioning
confidence: 99%
“…Neurophysiological testing and neurological examination have been well studied as useful indicators of outcomes (1,2). One particular examination finding of prognostic importance is early posthypoxic myoclonus (PHM).…”
mentioning
confidence: 99%